Revisiting the linkage between entrepreneurial intention and behavior in a mediated model: Evidence from Vietnamese logistics industry students - Ta Huy Hung (Problems and Perspectives in Management)
Young entrepreneurs are crucial participants in a country’s entrepreneurial ecosystem. This study analyzes the effects of entrepreneurial motivation and perceived university support on the entrepreneurial intention and behavior of Vietnamese students. A survey was conducted with 831 students who are studying logistics and supply chain management programs. Smart PLS and the Sobel test were utilized to validate the proposed hypotheses. The results indicate that financial motivation has a positive impact on student’s entrepreneurial intention and entrepreneurial behavior. Conversely, the desire for autonomy motivation has a direct negative impact on entrepreneurial behavior. Furthermore, perceived university support exerts a strong direct influence on student’s entrepreneurial intention and entrepreneurial behavior. Notably, entrepreneurial intention partially mediates the relationship between entrepreneurial motivation and entrepreneurial behavior and the relationship between perceived university support and entrepreneurial behavior. The research implications suggest that policymakers should prioritize assessing students’ entrepreneurial motivations before implementing entrepreneurship training programs. Additionally, universities should provide appropriate entrepreneurial support to students throughout their entrepreneurial behavior and their entrepreneurial careers. AcknowledgmentThis research is funded by the International School, Vietnam National University, Hanoi (VNU-IS) under project number CS.2023-12.